Attitudes and beliefs of little league baseball parents regarding sport specialization and college scholarship availability. Issue 6 (2nd November 2022) - Post, Eric G.; Rosenthal, Michael D.; Pennock, Andrew T.; Rauh, Mitchell J.
ABSTRACT: Objectives: Previous studies of parents of adolescent athletes identified a belief among parents of the importance of early specialization for skill development. However, it is unclear if these attitudes and beliefs are also held among parents of baseball athletes, which is the second-most popular boy's sport in the United States. The purpose of this study was to describe the knowledge, attitudes, and beliefs of parents of Little League baseball players regarding sport specialization and college scholarships. Methods: Two-hundred and forty-four parents of Little League baseball players (female parents: 60.7%, parent age: 41.1 ± 6.2 years old, male children: 98.0%, child age: 9.5 ± 1.6 years old) completed an anonymous online questionnaire regarding parent attitudes and beliefs on sport specialization and college scholarships. Results: Most parents (72.4%) felt that specialization would increase their child's baseball ability either 'quite a bit' or 'a great deal.' Fewer than half of all parents (42.0%) reported that specialization was either 'quite a bit' or 'a great deal' of a problem. Parents underestimated the availability of Division I college baseball scholarship availability (median [IQR]: 5 [4–10]), compared to the actual value of 11.7 scholarships per Division I roster. Only 10.2% of parents (N = 25) reported that they believed it was 'somewhat' or 'very' likely that their child would receive a college baseball scholarship. Conclusion: Further efforts are needed to understand parent attitudes and beliefs regarding sport specialization and college scholarships in various sports to better understand current trends in youth sport participation.